Genome sequence and overview of Oligoflexus tunisiensis Shr3T in the eighth class Oligoflexia of the phylum Proteobacteria. Issue 1 (December 2016) - Nakai, Ryosuke; Fujisawa, Takatomo; Nakamura, Yasukazu; Baba, Tomoya; Nishijima, Miyuki; Karray, Fatma; Sayadi, Sami; Isoda, Hiroko; Naganuma, Takeshi; Niki, Hironori
Abstract Oligoflexus tunisiensis Shr3T is the first strain described in the newest (eighth) classOligoflexia of the phylumProteobacteria . This strain was isolated from the 0.2-μm filtrate of a suspension of sand gravels collected in the Sahara Desert in the Republic of Tunisia. The genome ofO. tunisiensis Shr3T is 7, 569, 109 bp long and consists of one scaffold with a 54.3% G + C content. A total of 6, 463 genes were predicted, comprising 6, 406 protein-coding and 57 RNA genes. Genome sequence analysis suggested that strain Shr3T had multiple terminal oxidases for aerobic respiration and various transporters, including the resistance-nodulation-cell division-type efflux pumps. Additionally, gene sequences related to the incomplete denitrification pathway lacking the final step to reduce nitrous oxide (N2 O) to nitrogen gas (N2 ) were found in theO. tunisiensis Shr3T genome. The results presented herein provide insight into the metabolic versatility and N2 O-producing activity ofOligoflexus species.